2012
DOI: 10.1074/jbc.m112.342246
|View full text |Cite
|
Sign up to set email alerts
|

Structural Evidence That Colicin A Protein Binds to a Novel Binding Site of TolA Protein in Escherichia coli Periplasm

Abstract: Background: Colicins interact with Tol proteins in the periplasm to facilitate their killing of E. coli cells. Results: The N terminus of colicin A interacts with the C terminus of TolA through β-strand addition. Conclusion: Colicin A interacts with TolA at a novel binding site to promote cell killing. Significance: TolA is integral to cell entry of colicin A, providing information to refine current models… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 64 publications
0
25
0
Order By: Relevance
“…Tol-dependent colicins have been shown to interact with one or more of the Tol proteins during their translocation across the periplasm, showing some similarities with Tol-dependent filamentous phage uptake. In 2012, Li et al (28) demonstrated that a colicin A peptide (residues 53-107) binds on the convex face of TolAIII Ec , forming an intermolecular antiparallel ␤-sheet.…”
mentioning
confidence: 99%
“…Tol-dependent colicins have been shown to interact with one or more of the Tol proteins during their translocation across the periplasm, showing some similarities with Tol-dependent filamentous phage uptake. In 2012, Li et al (28) demonstrated that a colicin A peptide (residues 53-107) binds on the convex face of TolAIII Ec , forming an intermolecular antiparallel ␤-sheet.…”
mentioning
confidence: 99%
“…X-ray structures of ColB [25] and ColM [26] show something similar with their TonB epitopes interacting with structured regions of the same molecule and other N-terminal residues being more flexible. NMR reveals that the TolB epitope of ColA binds intramolecularly to a globular domain of the protein in solution [27], but the TolB epitope of ColE9 behaves differently [17,28]. The two tryptophan residues in its TolB epitope promote the formation of clusters [17,20] of interacting residues (Figure 2), which then interact with each other instead of with a globular domain of the colicin [17].…”
Section: The T-domains (Translocation Domains) Of Colicins Contain Lomentioning
confidence: 99%
“…The function of TolA is not fully understood, it is involved in the structural integrity of E. coli and related bacterial cell membranes. It is also involved in active transport across the membrane but can be parasitized by colicins produced by other E. coli resulting in the death of the cell (Li et al 2012). The Tol system also allows uptake of phage DNA, although generally deleterious imported DNA may contain genes that could give the cell an advantage.…”
Section: Discussionmentioning
confidence: 99%